Social Inequality, Cultural Diversity: A View in Education Sociology - Caride Carbonell (ENDLESS: INTERNATIONAL JOURNAL OF FUTURE STUDIES, 2022)
The purpose of this study is to analyze social inequality, cultural diversity from the point of view of Sociology of Education. This research uses qualitative research with descriptive analysis approach. The type of data used in this study is secondary data obtained from library research. The type of data presentation in this study uses a qualitative approach. Based on the results of the analysis, it can be concluded that integration must be won day by day with the exercise, by all, of solidarity and the will to negotiate, with the fight against all forms of exclusion and for a true equality of opportunities and civic and political rights. An active and unequivocal will is required on both sides to resolve the inevitable conflicts that will cause the diversity of values ​​and customs, but above all social and political inequality. In the integration process, it is a question of jointly creating a new social space, which will probably be governed by new norms, born of negotiation and the joint creativity of the members of the majority group and those belonging to the minority group. Integration, creativity and negotiation are, therefore, inseparable concepts.